An Improved Nonlinear Settlement Calculation Method for Soft Clay considering Structural Characteristics - Binhui Ma; Zhuo Li; Kai Cai; Zhiyong Hu; Minghua Zhao; Chengbin He; Bingchu Chen; Xiaocheng Huang (Geofluids)
The settlement calculation model for soft clay foundation is established based on Hooke’s law and the Duncan-Chang model. By introducing the concept of damage ratio, the method for determining the deformation modulus of soil before and after damage under load is presented, and a nonlinear settlement calculation method which considers the structural characteristics of soft clay is proposed. In the end, a practical engineering example is analyzed with the proposed method and some current methods for soft clay settlement calculation. The results indicated that the proposed method is feasible and applicable in practical engineering.